The Effect of Planting Media Type and Ab Mix Concentration on the Growth and Yield of Hydroponic Bok Choy (Brassica rapa L.) - Lelawati, Nur; Hafifah, Hafifah; Ismadi, Ismadi; Yusuf, Muhammad; Wirda, Zurrahmi (Yayasan Pertanian Tropika Indonesia (YPTI), 2021)
Vegetables are usually classified by the part of the plant used for food, which is an essential source of many nutrients, including vitamins A and C, potassium, calcium, dietary fiber, and folate. Leafy greens are an abundant source of vitamin A and iron. The lack of fertile agricultural land has led to a decrease in the area of agricultural land, resulting in a decrease in the well-being of farmers. However, plant cultivation using the hydroponic method can be applied to solve this problem. Hydroponics is a method of growing crops without soil. Hydroponic farming is clean, simple, and efficient. This research aims to determine the effect of planting media type and AB mix concentration on hydroponic bok choy. The research used a Completely Randomized Design (CRD) with two factors and three replications, resulting in 27 experimental units. The first factor was planting media (M): Rockwool (M1), husk charcoal (M2), and sand (M3). The second factor was AB mix concentrations: 3 ml/l (K1), five ml/l (K2), and seven ml/l (K3).